Respuesta :

Answer:

x = 3

Step-by-step explanation:

Simplifying

8 + -3x = 14 + -5x

Solving

8 + -3x = 14 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.

8 + -3x + 5x = 14 + -5x + 5x

Combine like terms: -3x + 5x = 2x

8 + 2x = 14 + -5x + 5x

Combine like terms: -5x + 5x = 0

8 + 2x = 14 + 0

8 + 2x = 14

Add '-8' to each side of the equation.

8 + -8 + 2x = 14 + -8

Combine like terms: 8 + -8 = 0

0 + 2x = 14 + -8

2x = 14 + -8

Combine like terms: 14 + -8 = 6

2x = 6

Divide each side by '2'.

x = 3

-18+(15x-6)+8
-18+15x+2
-16+15x
ACCESS MORE